Multiple Recurrent Bilateral Ovarian Teratomas: A Case Report and Comprehensive Review - Anužytė, Aušrinė; Noreikaitė, Eglė; Žitkutė, Viktorija; Andreika, Linas (Lietuvos chirurgija, 2025)
Background. Dermoid ovarian cyst or mature cystic teratoma is the most common subtype of ovarian germ cell tumors. These tumors are usually benign and contain hair, bone, primitive or mature teeth, cartilage, nerve and fat. The aim of this article is to present a case of multiple recurrent bilateral ovarian teratomas and to review literature on this topic. Case presentation. We present the case of a 25-year-old woman complaining of pain in the left abdomen, persisting for a year. All laboratory tests were within normal range, aside from elevated testosterone level. Intrauterine ultrasound and pelvic MRI revealed multiple dermoid cysts varying in size bilaterally. Laparoscopic ovarian cystectomy was performed and teratomas containing hair and fat were removed. During follow-up checkups a new 1 cm hyperechogenic mass, possibly a recurrent dermoid cyst, was observed in the right ovary. Conclusions. Ovarian dermoid cysts are a common benign ovarian tumor, usually found incidentally. They are often asymptomatic, occasionally presenting with abdominal pain or hormonal effects. The treatment strategy depends on many factors, but large, symptomatic cysts often require surgical management. Ovarian teratomas have a small chance of recurrence.
Keywords: dermoid ovarian cyst; mature cystic teratoma; laparoscopic ovarian cystectomy